Population And Development: Employing The Capability Approach in Family Planning Policy for Women In Indonesia - Julius Ary Mollet; Genoveva Chatleen C. Mollet (AIBPM Publisher, 2024)
Presently, Indonesia ranks as the fourth most populous country globally. The country's population is on a constant rise, accompanied by escalating issues such as poverty, hunger, gender inequality, and disparity. To address these challenges, a solution was initiated in the 1980s when the government first introduced a family planning program aimed at regulating the population's growth within the country. Employing the capability approach, this research examined the influence of Indonesia's family planning policy on women, offering a comprehensive viewpoint. Additionally, gender disparity emerges due to insufficient population and family development support for human rights. The conversion factors significantly affect the freedom capability and women's capacity to translate available resources into action. The purpose of this study is to critically discuss the strengths and weaknesses of Indonesia's family planning policy and its impact on women. The outcome indicated that obstacles for women arose from factors like shifts in governance, conflicting policies, government inefficiency, and BKKBN's incapacity to handle family planning. Consequently, it is crucial for all sectors and agencies to efficiently execute the family program to alleviate gender inequality in women's health.